2005
DOI: 10.1002/path.1824
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NOX1, a superoxide‐generating NADPH oxidase, in colon cancer and inflammatory bowel disease

Abstract: Reactive oxygen species (ROS) are at the centre of many physiological and pathological processes. NOX1, a ROS-producing NADPH oxidase, is highly expressed in the colon but its function in colonic physiology or pathology is still poorly understood. It has been suggested to play a role in host defence, but also in cell growth and possibly malignant transformation. In this study we characterized NOX1 expression in human colon samples derived from healthy control subjects and patients with colon cancer or inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 29 publications
5
148
2
2
Order By: Relevance
“…In many of cases, the source of this ROS is Nox enzymes: this includes melanoma (Nox4, [127]), prostate cancer (Nox5 [128] and Nox1 [129]), glioblastoma (Nox4 and sometimes Nox5 [130]), H. pylorusinduced gastric inflammation leading to gastric cancer (Nox1 [131]) and Barrett's esophageal adenocarcinoma (Nox5 [132]). Some, but not all reports have observed an increase in Nox1 expression in colon cancer, see [133][134][135][136]. In recent studies, we found that Nox1 protein and mRNA are over-expressed beginning at the adenoma (precancerous stage), and did not further increase at later stages [Laurent et al (unpublished data)], consistent with most other reports.…”
Section: A Association Of Ros Nox Enzymes and Cancersupporting
confidence: 92%
“…In many of cases, the source of this ROS is Nox enzymes: this includes melanoma (Nox4, [127]), prostate cancer (Nox5 [128] and Nox1 [129]), glioblastoma (Nox4 and sometimes Nox5 [130]), H. pylorusinduced gastric inflammation leading to gastric cancer (Nox1 [131]) and Barrett's esophageal adenocarcinoma (Nox5 [132]). Some, but not all reports have observed an increase in Nox1 expression in colon cancer, see [133][134][135][136]. In recent studies, we found that Nox1 protein and mRNA are over-expressed beginning at the adenoma (precancerous stage), and did not further increase at later stages [Laurent et al (unpublished data)], consistent with most other reports.…”
Section: A Association Of Ros Nox Enzymes and Cancersupporting
confidence: 92%
“…However, and in contrast to the effects of N1IC, we found that hes1 was not sufficient to induce tumor growth in vivo in the absence of ␤-catenin/TCF activity indicating that other Notch-targets down- stream of ␤-catenin participate in regulating colorectal tumorigenesis. Consistently, several of the identified Notch-target genes in our screening have been involved in different aspects of intestinal differentiation or cancer including SOX9 (38, 39) KLF5 (47), CD44 (32), or NOX1 (48). Mutations in the APC gene have been found in most sporadic colorectal tumors and in those arising in FAP patients.…”
Section: Discussionmentioning
confidence: 56%
“…Cependant plusieurs études récentes réfutent ce rôle pour Nox-1 dans les cancers colorectaux. Cette enzyme est exprimée à la fois dans les cryptes et les villosités intestinales [23], suggérant qu'elle jouerait un rôle préférentiel dans la différenciation plutôt que dans la prolifération.…”
Section: Prolifération Cellulaireunclassified